Selective six spectrophotometric methods for determination of remdesivir and moxifloxacin hydrochloride for COVID-19 treatment with overlapping spectra: a comprehensive evaluation of greenness, blueness, and whiteness - Eman A. Madbouly; Abdalla A. El-Shanawani; Sobhy M. El-Adl; Ahmed S. Abdelkhalek (BMC Chemistry)
Abstract Selective, and green spectrophotometric methods have been developed for the simultaneous analysis of remdesivir (RDV) and moxifloxacin hydrochloride (MFX), two active agents that are being used together in COVID-19 treatment. Because of the considerable spectral overlap, six mathematical spectrophotometric approaches were applied, including ratio derivative, ratio difference, mean centering of ratio spectra, area under the curve, Q-analysis, and bivariate calibration, to allow accurate interference-free determination without preliminary separation. The proposed methods were validated as per ICH guidelines, demonstrating excellent linearity over the concentration ranges of 1–15 µg/mL for RDV and 1–10 µg/mL for MFX, with correlation coefficients exceeding 0.999. They showed high sensitivity with LODs from 0.26 to 0.92 µg/mL and LOQs from 0.27 to 0.96 µg/mL for both drugs, enabling reliable trace analysis of the studied drugs in complex matrices. The methods also applied to dosage forms and spiked human plasma provided good recoveries with minimal matrix interference, demonstrating that the methods are robust and applicable. Eco-Scale, ComplexGAPI, and AGREE gave a high score on green profiles for environmental and practical sustainability. Further, the high whiteness and blueness scores indicated that the methods met the requirements of white analytical chemistry by RGB12 and BAGI tools. Thus, these methods offer a practical, eco-conscious solution for simultaneous determination of RDV and MFX in pharmaceutical and clinical settings, contributing to better therapeutic monitoring in COVID-19 management.